Rural education and empowerment in Uruguay - Rodríguez Giménez, Mariana Soledad (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
This essay aims to provide an analytical and critical look at the Uruguayan rural educational system from its beginnings to the present, trying to find in an analytical and critical way elements that allow it to be positioned as a strategy for the empowerment or transformation of a sector of society. as particular as it is necessary in the second smallest country in South America, constituting 8 % of the country’s inhabitants, positioning Uruguay in first place in the international ranking with the smallest rural population in the world with respect to its total population, but a fundamental sector for an economy in which 9 of the 10 main exported products are of agricultural origin. The Uruguayan rural educational system, since its origins, has been able to advance, it has been left aside from public policies, it has been violated, it has been dismantled, it has evolved, it has gone backwards, but it has found, thanks to the human capacity to transform and empower itself, reasons for struggle, resistance and permanence.